Book Review: Negotiating Women’s Veiling, Politic & Sexuality in Contemporary Indonesia - Qibtiyah, Alimatul (Sunan Kalijaga State Islamic University & The Asia Foundation, 2014)
Judul Buku : Negotiating Womenâ€™s Veiling, Politic & Sexuality in Contemporary IndonesiaPenulis : Dewi CandraningrumPenerbit : @IRASEC, Juni 2013ISBN :Â 978-616-7571-15-7Tebal halaman : 89 halaman